CQD-based electrochemical immunosensor for sensitive D-dimer detection in thrombosis and COVID-19 - Jillian Gamboa; Carmen Linares; Virginia Cebrián; Hamidreza Enshaei; Óscar Ahumada; Francesc Estrany; Juan Torras (Sensing and Bio-Sensing Research)
Thrombosis, a leading cause of heart attacks, strokes, and venous thromboembolism (VTE), contributes to 25 % of global deaths. Factors like aging and immobility increase VTE risk. D-dimer (DD), whose elevated levels indicate conditions such as pulmonary embolism and severe COVID-19, is a key biomarker for thrombus detection, predicting higher mortality risks. Traditional DD detection methods are time-consuming and costly. Emerging point-of-care (POCT) biosensors offer faster, cost-effective alternatives, utilizing electrochemical or optical detection and nanostructured films. This study aims to develop a sensitive, label-free electrochemical immunosensor for DD detection using carbon quantum dots (CQDs) functionalized electrodes and electrochemical impedance spectroscopy (EIS). CQDs enhance electrode sensitivity by improving conductivity and providing anchoring sites for monoclonal antibody (Ab). The biosensor was made by activating a carbon screen printed electrode with KOH, adding amino groups via 3-Aminopropyltriethoxysilane, linking CQDs with 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide/N-hydroxysuccinimide (EDC/NHS), and immobilizing DD Ab on CQD surface. Raman spectroscopy and EIS confirmed successful functionalization and increased resistance with Ab and bovine serum albumin layers. The biosensor effectively detected DD antigens, with a calibration curve ranging from 10 to 1000 ng mL−1 and a low limit of detection of 13.4 ng mL−1. CQDs improved sensitivity, and low Ab concentrations reduced costs. This CQD-based impedance immunosensor offers a practical approach for early thrombosis detection and monitoring diseases like VTE and COVID-19 at the point of care.